Dynamic membrane interactions of antibacterial and antifungal biomolecules, and amyloid peptides, revealed by solid-state NMR spectroscopy - Naito, Akira; Matsumori, Nobuaki; Ramamoorthy, Ayyalusamy (Biochimica et biophysica acta. General subjects, 2018)
A variety of biomolecules acting on the cell membrane folds into a biologically active structure in the membrane environment. It is, therefore, important to determine the structures and dynamics of such biomolecules in a membrane environment. While several biophysical techniques are used to obtain low-resolution information, solid-state NMR spectroscopy is one of the most powerful means for determining the structure and dynamics of membrane bound biomolecules such as antibacterial biomolecules and amyloidogenic proteins; unlike X-ray crystallography and solution NMR spectroscopy, applications of solid-state NMR spectroscopy are not limited by non-crystalline, non-soluble nature or molecular size of membrane-associated biomolecules. This review article focuses on the applications of solid-state NMR techniques to study a few selected antibacterial and amyloid peptides. Solid-state NMR studies revealing the membrane inserted bent α-helical structure associated with the hemolytic activity of bee venom melittin and the chemical shift oscillation analysis used to determine the transmembrane structure (with α-helix and 310-helix in the N- and C-termini, respectively) of antibiotic peptide alamethicin are discussed in detail. Oligomerization of an amyloidogenic islet amyloid polypeptide (IAPP, or also known as amylin) resulting from its aggregation in a membrane environment, molecular interactions of the antifungal natural product amphotericin B with ergosterol in lipid bilayers, and the mechanism of lipid raft formation by sphingomyelin studied using solid state NMR methods are also discussed in this review article. This article is part of a Special Issue entitled "Biophysical Exploration of Dynamical Ordering of Biomolecular Systems" edited by Dr. Koichi Kato. [Display omitted] •Melittin in a membrane environment is a pseudo-transmembrane bending α-helix structure.•Alamethicin is a transmembrane structure with α-helix and 310-helix in N- and C-termini.•Membrane interaction is key for human-IAPP induced islet cell toxicity.•Amphotericin B ergosterol complex takes both parallel and anti-parallel orientation.•Hydrogen-bond network among sphingomyelin is important for raft formation.